2022
DOI: 10.3390/su14020736
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Food Consumption Values of Vietnamese Consumers on the Reliability and Purchase Intention of Korean Home Meal Replacements

Abstract: The Vietnamese home meal replacement (HMR) market is expected to face intensified competition due to economic development and urbanization. This study analyzes how the food consumption values of Vietnamese consumers affect the perceived reliability and intention to purchase Korean food in the form of HMRs and provides basic data to establish strategies for Korean HMRs to secure an advantage in an intensely competitive market. A survey was conducted with Vietnamese consumers who had used Korean HMRs before and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
1
1
0
Order By: Relevance
“…Therefore, the results are consistent with the literature, suggesting that eco-friendly distribution significantly determines consumers' purchasing intention. The findings of this study complement the previous studies of ( Wang et al, 2020;Li et al, 2018;Choi & Lee, 2017;Carrington et al, 2016;Maignan & Ferrell, 2004). These researchers have made a sound conviction that a significant strong positive relationship exists between eco-friendly distribution and consumer purchasing intention On the other hand, this study nullifies the outcomes of previous research (Kim et al, 2017;Yeo & Goh, 2015), which found an insignificant relationship between ecofriendly distribution and consumer purchase intention.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, the results are consistent with the literature, suggesting that eco-friendly distribution significantly determines consumers' purchasing intention. The findings of this study complement the previous studies of ( Wang et al, 2020;Li et al, 2018;Choi & Lee, 2017;Carrington et al, 2016;Maignan & Ferrell, 2004). These researchers have made a sound conviction that a significant strong positive relationship exists between eco-friendly distribution and consumer purchasing intention On the other hand, this study nullifies the outcomes of previous research (Kim et al, 2017;Yeo & Goh, 2015), which found an insignificant relationship between ecofriendly distribution and consumer purchase intention.…”
Section: Discussionsupporting
confidence: 92%
“…On the one hand, research has shown that eco-friendly distribution practices can increase consumers' purchase intention (Wang et al, 2020;Carrington et al, 2016). Additionally, (Choi & Lee, 2017) found a significant positive relationship between ecofriendly distribution and consumers' purchase intention in a study of consumers in South Korea. The authors suggest that eco-friendly distribution practices increase consumers' perceived product value and purchase intention.…”
Section: Relationship Between Eco-friendly Distribution and Consumers...mentioning
confidence: 99%